2019
DOI: 10.33594/000000103
|View full text |Cite
|
Sign up to set email alerts
|

Renal Fibrosis, Immune Cell Infiltration and Changes of TRPC Channel Expression after Unilateral Ureteral Obstruction in Trpc6-/- Mice

Abstract: This article is licensed under the Creative Commons Attribution-NonCommercial-NoDerivatives 4.0 International License (CC BY-NC-ND). Usage and distribution for commercial purposes as well as any distribution of modified material requires written permission.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 77 publications
2
29
0
Order By: Relevance
“…In our previous study, we have shown that TRPC6 contributes to renal fibrosis and immune cell infiltration in a murine UUO model using Trpc6 −/− mice 9 . Renal IRI is a common cause of CKD.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In our previous study, we have shown that TRPC6 contributes to renal fibrosis and immune cell infiltration in a murine UUO model using Trpc6 −/− mice 9 . Renal IRI is a common cause of CKD.…”
Section: Discussionmentioning
confidence: 97%
“…In our study, Trpc6 −/− mice subjected to acute IRI showed no difference in renal function or tubular damage when compared to WT mice which underwent IRI. The Trpc6 −/− mouse model was established as a homozygous colony, therefore we used C57BL/6 J mice as control 9 . Given this limitation of our experimental approach and to account for possible confounding genomic and non-genomic effects of other TRPC channels caused by global loss of TRPC6 31 , we performed also studies using two different TRPC6 blockers SH045 and BI-749327 in C57BL/6 J WT mice to evaluate the role of TRPC6 in short-term AKI outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…qRT-PCR was performed as described previously [ 26 ]. Total RNA from snap-frozen kidneys or HK-2 cells was isolated using an RNeasy RNA isolation kit (Qiagen, Australia).…”
Section: Methodsmentioning
confidence: 99%